The relative representation of ecosystem services and disservices in South African newspaper media. Issue 1 (1st January 2019) - McLellan, V.; Shackleton, C.M.
ABSTRACT: Newspapers are key information sources and may influence both public opinion and policy. Previous studies have analysed the portrayal of ecosystem disservices in newspapers, but none have assessed the relative coverage between disservices and services, or how it might have changed over time. We report on the relative frequency and depiction of ecosystem services and disservices in South African, English newspapers over a 15-year period. We used a SABINET search complemented by key-informant interviews with environmental journalists. For each article we recorded if it covered ecosystem services or disservices, the type of service or disservice, and article tone and length. Overall, 2, 201 articles were found, of which 25% were on services and 75% on disservices. The number of articles per year declined over the 15-year period for services, but not disservices. The most common services were energy and craft materials, food production, recreation and culture, and disservices were human health, heat waves and floods. Articles on ecosystem services were 25–40% longer than those on disservices. Article lengths on both declined over the 15 years. The greater reporting of ecosystem disservices over services is likely to influence public opinion and environmental decision-making accordingly. EDITED BY Kurt Jax